Human Rights: Illusion or Reality; Theological (Shiite) Perspective (Part 2) - Jamkarani, Ali (Bangladesh Journal of Bioethics, 2015)
The discussion is based around these issues, history of Human Rights, timeline for Human Rights history, question asked in this regard and enemy and friend of human rights. Describing the problems and its resolve from logical reasoning perspective; intellectual argumentation based on logical reason of, what is universal human right, democracy and illegal wars in the world by super powers as example America? Attempt to describe the inner construction of a human being-perfection-. Introduction to the concept of infallibility in different parts in the article, purify yourself and being purified. What is it, is it possible for a creation named human to be not fallible, is the idea or practicing it impossible or there is a great sphere of being able to practicing it and reaching the status if one finds guidance for the right way with peace and human rights prevailed in the world. Majority of the thought in the text, based on hadith-tradition- from the Prophet of Islam Peace upon Him and His family Ahl al-Bait Peace upon Them.